Effectiveness of a polycaprolactone scaffold combined with platelet-rich fibrin as guided tissue regeneration materials for preserving an implant-supported overdenture - Lobna Mohamed Abdel-Aziz; Shahenda A. Abdallah; Noura Mohammed bakr; Sara M. Bahaa; Ebtihal H. Zainalabdeen; Monther Alsharif; Shadia A. Elsayed (Elsevier, 2024)
Objectives: This study aimed to assess the effectiveness of ridge preservation using a polycaprolactone (PCL) scaffold combined with platelet-rich fibrin (PRF) to promote bone regeneration before implantation. Materials and Methods: This prospective study was conducted at Al-Azhar University in Egypt. It included 30 participants requiring the extraction of their last mandibular premolar before constructing an implant-supported overdenture. The participants were divided into three groups: Group A was treated with a PCL scaffold and PRF as ridge preservative materials, Group B was treated with PRF alone, and Group C (control) was treated with no preservative material. Bone samples were collected for histomorphometric analysis at implant placement. Results: The participants' mean age was 65.3 ± 4.27 years, and 18 (60%) were male. Postoperative alveolar bone lengths differed significantly between Groups A and B (P = 0.001). However, alveolar bone width changes did not differ significantly among groups. In contrast, the postoperative bone density and loss differed significantly among groups (P = 0.001). Conclusion: Combining two ridge preservation techniques (PCL and PRF) enhanced participants' alveolar bone remodelling by decreasing its resorption and maintaining its width.